2020
DOI: 10.1021/acs.molpharmaceut.0c00096
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-in-Cyclodextrin-in-Liposomes: Formulation Development and Interactions with Model Bacterial Membranes

Abstract: Gram-negative bacteria possess numerous defenses against antibiotics, due to the intrinsic permeability barrier of their outer membrane, explaining the recalcitrance of some common and life-threatening infections. We report the formulation of a new drug, PPA148, which shows promising activity against all Gram-negative bacteria included in the ESKAPEE pathogens. PPA148 was solubilized by inclusion complexation with cyclodextrin followed by encapsulation in liposomes. The complex and liposomal formulation presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Here we focused on the contribution of NR to the analysis of asymmetric membrane models at the solid/liquid interface, which is a clear example of a case of study in which no other structural techniques could be employed. The combination of NR and in vitro OM models has shown a clear potential for the investigation of LPS and the asymmetric OM structure [52,56,57,68], its interaction with antimicrobials [25][26][27][28][29] and drug delivery systems [70]. The majority of the present studies have focused on rough LPS species due to their well-defined structures but the recent work by the group of Schneck et al has demonstrated the possibility to assemble stable smooth LPS layers both at the air/water [57] and at the solid/liquid interface [76].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we focused on the contribution of NR to the analysis of asymmetric membrane models at the solid/liquid interface, which is a clear example of a case of study in which no other structural techniques could be employed. The combination of NR and in vitro OM models has shown a clear potential for the investigation of LPS and the asymmetric OM structure [52,56,57,68], its interaction with antimicrobials [25][26][27][28][29] and drug delivery systems [70]. The majority of the present studies have focused on rough LPS species due to their well-defined structures but the recent work by the group of Schneck et al has demonstrated the possibility to assemble stable smooth LPS layers both at the air/water [57] and at the solid/liquid interface [76].…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, a different group combined AFM and NR to investigate the effects of two types of plasticins on asymmetric OM models, highlighting once again the importance of the cationic nature of these type of antimicrobial peptides for their interaction with the OM [69]. More recently, Vandera et al [70] implemented, for the first time, the use of PL/LPS bilayers to address the fusion mechanism of a bacterial drug delivery system with its model OM target. Alongside with complementary microbiological assays, NR provided novel structural insights into the initial stages of translocation of a fluidosome-based drug carrier across the Gram-negative surface.…”
Section: Supported Pl/lps Asymmetric Bilayersmentioning
confidence: 99%
“…Many experiments have been performed on model bacterial membranes, most often simulated by monolayers composed of mixtures of phospholipids such as DMPE, DMPG, and CL at different proportions [98]. The interactions of antibiotics with model bacterial membranes with the use of E. coli extract, LPSs, or dioleoylphosphatidylcholine (DOPC) dissolved in CHCl 3 solution have been reported in [64,99,100]. The contents of individual phospholipids in the membrane are very important because changes in the composition of acyl chains or head groups impact the bilayer fluidity and stability; consequently, they affect the membrane response to environmental perturbations [101].…”
Section: Langmuir Monolayer As a Model Bacterial Membranementioning
confidence: 99%
“…Benefiting from these advantages, liposomes can overcome host biomembrane barriers or biofilms generated by multidrug-resistant strains, delivering antimicrobial agents directly to bacteria [ 196 , 197 ]. In addition, liposomes have been reported to successfully combat the outer membrane barrier of Gram-negative bacteria and deliver antibiotics into bacterial cells for significantly improved activity [ 198 ]. Being supplemented with surface chemistry and/or other nanomedical techniques enables liposomes to be smart-responsive nanoplatforms which provide controlled, on-demand, and/or spatiotemporal release of antimicrobials.…”
Section: Nanotherapeutic Platforms For Sepsis Treatment Through Targementioning
confidence: 99%